Prevention Practice of COVID-19 Using Personal Protective Equipment and Hand Hygiene Among Healthcare Workers in Public Hospitals of South Wollo Zone, Ethiopia - Awoke Keleb; Ayechew Ademas; Mistir Lingerew; Tadesse Sisay; Gete Berihun; Metadel Adane (Frontiers Media S.A., 2021)
Objective: The use of personal protective equipment and hand hygiene are often the most recommended line of defense against coronavirus disease-19 (COVID-19). The purpose of this study is to determine the magnitude of compliance and associated factors of personal protective equipment (PPE) utilization and hand hygiene practice among healthcare workers in public hospitals of South Wollo Zone, Northeastern Ethiopia.Methods: A hospital-based cross-sectional study was conducted among 489 healthcare workers in public hospitals of South Wollo Zone, Northeastern Ethiopia from June 15 to July 30, 2021. Proportional sample size allocation to each selected hospital followed by simple random sampling techniques were used to select the study participants using human resource records from each hospital. A pre-tested and structured self-administered questionnaire with WHO's standardized hand hygiene and PPE utilization observational checklist were used to collect data. Bivariate and multivariable analyses with 95% CI and p-value < 0.05 were employed to identify the associated factors of personal protective equipment utilization.Results: About 32 and 22.3% of healthcare workers were compliant with personal protective equipment utilization and hand hygiene practice, respectively. Feedback for safety (AOR = 2.05; 95% CI: 1.26-3.35), training on COVID-19 prevention (AOR = 3.43; 95% CI: 2.01-5.86), and perception to infection risk (AOR = 1.98; 95% CI: 1.18-3.33) were significant factors of good compliance with personal protective equipment utilization.Conclusion: The magnitude of good compliance with personal protective equipment utilization and hand hygiene was low. Interventions to promote personal protective equipment utilization and hand hygiene should focus on feedback for safety, training on COVID-19 prevention, and perception of infection risk.